2021
DOI: 10.1097/olq.0000000000001434
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydial Pgp3 Seropositivity and Population-Attributable Fraction Among Women With Tubal Factor Infertility

Abstract: Chlamydia trachomatis Pgp3 seropositivity is associated with tubal factor infertility (TFI) in nonblack women without endometriosis. Past chlamydial infection may account for TFI in 20% of these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(73 reference statements)
1
2
0
Order By: Relevance
“…We found that Pgp3 IgG1 ELISA exhibited superior sensitivity for detecting IgG1 in these women with different CT infection outcomes compared to IgG1 ELISAs using other CT antigens and CT EBs. Over the past 15 years, CT Pgp3 has emerged as the most consistently targeted CT antigen in CT total IgG ELISAs (Wills et al, 2009;Horner et al, 2016;Anyalechi et al, 2022). We confirmed this finding of exceptional immunogenicity in this study by showing 97.5% IgG1 seropositivity in women with CT infection outcomes.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We found that Pgp3 IgG1 ELISA exhibited superior sensitivity for detecting IgG1 in these women with different CT infection outcomes compared to IgG1 ELISAs using other CT antigens and CT EBs. Over the past 15 years, CT Pgp3 has emerged as the most consistently targeted CT antigen in CT total IgG ELISAs (Wills et al, 2009;Horner et al, 2016;Anyalechi et al, 2022). We confirmed this finding of exceptional immunogenicity in this study by showing 97.5% IgG1 seropositivity in women with CT infection outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…These outcomes included persisting infection versus spontaneous resolution documented at the time of returning for treatment of a positive CT screening test and among those with persisting infection at the time of treatment, the outcome reinfection vs. no reinfection at a 3-month follow-up visit. While IgG antibodies to some of these 9 CT antigens have been previously studied (Tan et al, 2009;Anyalechi et al, 2022;Marques et al, 2022), to our knowledge, this is the first report evaluating IgG1 responses to these antigens and comparing antibody responses to these 9 CT antigens between distinct groups with different CT infection outcomes. We found that Pgp3 IgG1 ELISA exhibited superior sensitivity for detecting IgG1 in these women with different CT infection outcomes compared to IgG1 ELISAs using other CT antigens and CT EBs.…”
Section: Discussionmentioning
confidence: 94%
“…This is further supported by an earlier study in which we found no difference in CT seropositivity frequency based on CT EB ELISA in Black women enrolled at clinics in 2 US cities (Birmingham and Pittsburgh) with tubal factor infertility versus other infertility etiologies (81% vs. 78%) 14 ; in this same cohort of Black women, another CT antibody assay, a CT Pgp3 ELISA, was also not associated with tubal factor infertility. 15 Thus, CT serological assays that are more specific for CT-associated upper genital tract pathology will be needed for future studies aimed at better understanding the contribution of chlamydia toward reproductive complications in populations of women with high frequency of CT infections.…”
Section: Discussionmentioning
confidence: 99%